Culture and mental health - Londoño Bernal, Laura Victoria (Poiésis, 2012)
During the development of this essay we are going to analyze the characteristic elements of modern culture and the ways the illness or mental pathology appears in the humans immersed in the culture, and the way that psychology responds to the emergence of this pathologies in a period dominated by capitalism. It intends to make an articulation of concepts such as mental health, mental pathologies, subjectivity and culture.